The simulation research of dissolved nitrogen and phosphorus non-point source pollution in Xiao-Jiang watershed of Three Gorges Reservoir area - Wu, Lei (Water science and technology : a journal of the International Association on Water Pollution Research, 2010)
Xiao-jiang, with a basin area of almost 5,276 km(2) and a length of 182.4 km, is located in the center of the Three Gorges Reservoir Area, and is the largest tributary of the central section in Three Gorges Reservoir Area, farmland accounts for a large proportion of Xiao-jiang watershed, and the hilly cropland of purple soil is much of the farmland of the watershed. After the second phase of water storage in the Three Gorges Reservoir, the majority of sub-rivers in the reservoir area experienced eutrophication phenomenon frequently, and non-point source (NPS) pollution has become an important source of pollution in Xiao-jiang Watershed. Because dissolved nitrogen and phosphorus non-point source pollution are related to surface runoff and interflow, using climatic, topographic and land cover data from the internet and research institutes, the Semi-Distributed Land-use Runoff Process (SLURP) hydrological model was introduced to simulate the complete hydrological cycle of the Xiao-jiang Watershed. Based on the SLURP distributed hydrological model, non-point source pollution annual output load models of land use and rural residents were respectively established. Therefore, using GIS technology, considering the losses of dissolved nitrogen and phosphorus in the course of transport, a dissolved non-point source pollution load dynamic model was established by the organic coupling of the SLURP hydrological model and land-use output model. Through the above dynamic model, the annual dissolved non-point source nitrogen and phosphorus pollution output as well as the load in different types were simulated and quantitatively estimated from 2001 to 2008, furthermore, the loads of Xiao-jiang Watershed were calculated and expressed by temporal and spatial distribution in the Three Gorges Reservoir Area. The simulation results show that: the temporal changes of dissolved nitrogen and phosphorus load in the watershed are close to the inter-annual changes of rainfall runoff, and the different land-use type distribution has great impacts on the spatial changes of dissolved nitrogen and phosphorus load in the watershed; The nitrogen and phosphorus load of different land-use types in size with descending order is, glebe and mixed land, paddy, grassland, urban land, forestland; however, for the phosphorus load, the unit area output load of glebe and mixed land is almost the same as for paddy fields; The output contribution of nitrogen and phosphorus pollution load from land-use accounts for 78%-85%, while the output contribution from livestock and poultry occupies 13%-20%. The established load model was verified by observation data, simulation results show that the established model is reasonable, simulation accuracy is higher